THE IMPACT OF ISRAELI FOREIGN POLICY IN CENTRAL ASIA: THE CASE OF UZBEKISTAN - BOUCEK, Christopher (CENTRAL ASIA AND THE CAUCASUS, 2004)
The demise of the Soviet Union, and the emancipation of its Central Asian republics, has led numerous authors and pundits to herald the arrival of a revived “Great Game;” a now global competition for influence and strategic access. The relative merits and advantages of a wide range of actors has heretofore been chronicled: the Unit-ed States, Russian Federation, People’s Republic of China, Turkey, Islamic Republic of Iran, and even Saudi Arabia, Pakistan, and India. To date, however, there has been little attention focused on the role of the State of Israel in the former Soviet South. Curiously, it is the State of Israel that has quietly developed the closest and greatest relations with the Muslim republics of Central Asia and the Caucasus. Within the last decade, the State of Israel has established extremely close relations with the newly independent nations of the region. By following Israel’s traditional foreign policy objectives, Tel Aviv has succeeded where other nations have floundered. In a relatively short time, it has achieved very close diplomatic, economic, and security ties with Central Asia, virtually unnoticed by the outside world. Israel has become a very successful player in Central Asia, influencing everything from pipeline construction to defense spending. Therefore, understanding the actions and intentions of this little studied actor is rapidly growing in importance as the region continues to evolve. It is the aim of this article to analyze and evaluate the role of Israeli foreign policy in Uzbekistan, and its impact on the region with a special emphasis on regional stability.